2018
DOI: 10.1016/j.kontakt.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of teaching first aid to 5-6 year old children - a longitudinal study

Abstract: Objective: Basic lifesaving activities should be taught in early childhood to develop helping attitude. Our goal was to teach up-to-date theoretical and practical basic first aid using the method of play for kindergarten children. Methods: 51 children visiting kindergarten in two areas of Hungary were involved in the survey, which took place between September and November 2011. The training consisted of two sessions with theoretical and practical games about first aid. As well as the first steps, which concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
3
0
9
Order By: Relevance
“…As 13 publicações incluídas no estudo foram produzidas de 2013 a 2018. Cinco (38,46%) [9,12,16,19,20] foram publicadas nos Estados Unidos da América, quatro (30,76%) [11,14,17,21] no Reino Unido, três (23,07%) [13,15,18] no Brasil e um (7,69%) [10] na República Tcheca. O Quadro 1 apresenta a descrição dos estudos incluídos na revisão segundo ano de publicação, país, referência, estratégias metodológicas e profissionais que utilizaram essas estratégias.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…As 13 publicações incluídas no estudo foram produzidas de 2013 a 2018. Cinco (38,46%) [9,12,16,19,20] foram publicadas nos Estados Unidos da América, quatro (30,76%) [11,14,17,21] no Reino Unido, três (23,07%) [13,15,18] no Brasil e um (7,69%) [10] na República Tcheca. O Quadro 1 apresenta a descrição dos estudos incluídos na revisão segundo ano de publicação, país, referência, estratégias metodológicas e profissionais que utilizaram essas estratégias.…”
Section: Resultsunclassified
“…As principais intervenções encontradas nesta revisão foram: elaboração de situações problemas [9,10,13,14,18], uso de jogos [10][11][12]16,17,19] e manequins [9,[12][13][14]19,21], elaboração de exercícios e discussão em grupo [13,14,16,18], uso do DEA [9,14,19] e da conversa interativa [10,13,15]. Em consonância com os achados deste trabalho, um estudo exploratório realizado em duas escolas do estado do Ceará, com 70 alunos do ensino fundamental, utilizou aulas expositivas, manequins e vídeos no ensino de primeiros socorros, evidenciando a melhoria no aprendizado após a aplicação da intervenção por enfermeiras e graduandos de enfermagem treinados previamente pelo Serviço de Atendimento Móvel de Urgência (SAMU) [23].…”
Section: Discussionunclassified
“…", and "Squeeze my hand"). Studies have shown that schoolchildren do not have problems in correctly assessing consciousness [24,26,70,71].…”
Section: Consciousnessmentioning
confidence: 99%
“…Gamification, popularly defined as "the use of game design elements in non-game contexts," [20] has emerged as a means of harnessing competitiveness by integrating gamification elements such as leaderboards, rewards, badges, avatars, and competitions to engage and motivate consumers [21,22]. The most common tools for teaching BLS to schoolchildren include self-made games [23][24][25], posters [26], songs [27], and manikins [23,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research has proven that preschool children are responsive not only to the formation of habits related to prevention, but also to the recognition of changes in condition due to accidents and to the acquisition of basic first aid knowledge as well [14].…”
Section: The System Of Early Childhood Education In Hungarymentioning
confidence: 99%